Nanobiochar: production, properties, and multifunctional applications - Ramanayaka, Sammani; Vithanage, Meththika; Alessi, Daniel S; Liu, Wu-Jun; Jayasundera, Anil C. A; Ok, Yong Sik (Environmental Science: Nano, 2020)
Nanobiochar has received much attention recently among engineered biochar types owing to its useful chemical and physical properties. Research efforts have attempted to discover novel methods for nanobiochar preparation and applications. In this review, we summarize the literature on various aspects of nanobiochar preparation, production and use. Often, the bulk parent biochar is obtained from biomass pyrolysis, and mechanically ground using different milling processes to fabricate nanobiochar. Apart from mechanical means, direct fabrication of nanobiochar through flash heating resulting in graphitic nanosheets has been reported. Process conditions applied to the parent biochar directly influence the properties of the resulting nanobiochar. For instance, over 70% of 33 nanobiochar samples derived from biomass pyrolyzed above 450 °C demonstrated 32 times greater BET specific surface areas than nanobiochar produced at <450 °C. Nanobiochar has diverse applications, such as in wastewater treatment, health care applications, use as an electrode material, and in supercapacitors and sensors, owing to its wide range of physical and chemical properties. However, the toxicity of nanobiochar to human and ecosystem health has not received sufficient research attention. More research should be performed to elucidate the drawbacks, such as the high agglomeration potential and low yield, of nanobiochar for practical uses. Furthermore, reported data are insufficient to obtain a clear idea of the nature and behavior of nanobiochar, despite the growing interest in the research topic. Hence, future research should be driven towards exploring techniques to improve the yield of nanobiochar, reduce agglomeration, upscale it for electrode supercapacitor production and understand toxicological aspects. Biochar conversion into nanobiochar induced multiple potential applications as an adsorbent, sensor, capacitor, and photocatalytic and plant nanobionic material.